GRACE Application to the Receding Lake Victoria Water Level and Australian Drought - Awange, Joseph; Sharifi, M.; Keller, W.; Kuhn, Michael (Springer, 2009)
Lake Victoria in Africa, the world’s second largest freshwater lake, has been experiencing receding water levels since 2001. As it recedes, more than 30 million people who depend on it for livelihood are facing a disaster. Similarly, Australia is facing its worst drought on record with the livelihoods of a few million people at stake. Gravity Recovery And Climate Experiment (GRACE) data for 45 months (i.e., April 2002–April 2006) are employed to analyze these emerging challenges by measuring variations in the stored water. The results indicate a general decline in the lake Victoria basins water level at a rate of 1.83 km3/month.